The improvisation of musical dialogue : a phenomenology of music - Benson, Bruce Ellis, 1960- (Cambridge University Press, 2003)
This book is an important contribution to the philosophy of music. Bruce Benson's concern is the phenomenology of music making as an activity. He offers a radical thesis that it is improvisation that is primary in the moment of music making. It will be a provocative read.